Semi-supervised Clustering of Facial Expressions - Jalal, Ahsan (2017)
A Master of Science thesis in Electrical Engineering by Ahsan Jalal entitled, "Semi-supervised Clustering of Facial Expressions," submitted in November 2017. Thesis advisor is Dr. Usman Tariq. Soft and hard copy available.